On the dual reactivity of a nucleophilic dihydrido-diborane: reaction at the B−B bond and/or the B−H bond - Widera, Anna; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (Chemistry - a European journal, 2018)
The electron-rich, double-base stabilized dihydrido-diborane(4) [HB(hpp)]2 (hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) combines two different, easily accessible reactive sites: the B−B and B−H bond. Herein, we report two basically similar reactions of [HB(hpp)]2 with catecholborane and B-chlorocatecholborane unsuspectedly resulting in two different reactivities. While reaction of the diborane with two equivalents of HB(cat) proceeded with formation of a cationic triborane with a (3c2e) bond, [HB(μ-hpp)2(μ-BH2)]+, reaction with ClB(cat) led to hydride-chloride substitution yielding [ClB(hpp)]2. The cationic triborane was also obtained by the addition of BH3 to the in situ generated [HB(hpp)2B]+. Proceeding from the new compound [ClB(hpp)]2, we investigated its reactivity towards chloride abstraction with AlCl3 and GaCl3. Irrespectively of the salt chosen, the reaction led to formation of a radical tricationic tetraborane [B(hpp)4].3+ with a (4c,5e) bond. Moreover, the dichloro-diborane proves as a versatile reagent for further substitution cleanly reacting with the strong nucleophile nBuLi to a new dibutyl-diborane [nBuB(hpp)]2.
First published: 20 November 2017
Gesehen am 07.05.2018